Current Concepts in Endometrial Cancer - Patni, Ranu (Springer Singapore : Imprint: Springer, 2017)
This book comprehensively covers endometrial carcinoma, a type of gynecological cancer that is often overlooked but of great interest. Although the incidence of the disease is rapidly increasing, both per se and as part of familial cancer syndromes, there is a great deal of controversy regarding its diagnosis, evaluation and management. This book underlines the significance of endometrial carcinoma, highlights key prevention measures, charts its evaluation, and addresses the stage-by-stage management of this malignancy, with particular attention to the role of minimally invasive surgery. Further, it includes a chapter on future perspectives including robotics, targeted therapies and other developments in the offing. Overall, the book provides a comprehensive guide to endometrial cancer, which if approached properly, can have an excellent prognosis, thus saving many lives and/or achieving substantially improved quality of life.>.